2021
DOI: 10.3389/fmed.2021.764849
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Nuclear Medicine Examinations and Subsequent Risk of Neoplasm: A Nationwide Population-Based Cohort Study

Abstract: Objective: To evaluate the association between radiation exposure from repeated nuclear medicine (NM) examinations and the subsequent risk of neoplasm in pediatric patients.Methods: From 2000 to 2017, participants under 18 years of age who underwent NM scanning were identified using the Health and Welfare Data Science Center (HWDC) dataset, which was extracted from the Taiwan National Health Insurance Research Database (NHIRD). Both the exposed cohort and unexposed subjects were followed up with until the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In addition to young age, female sex was also mentioned as an important risk factor, but while the studies on cancer incidence following Chernobyl agree that there is a significant negative correlation between age of exposure and elevated radiation-attributable thyroid cancer incidence [ 12 , 13 , 14 , 15 ], sex differences and hormonal effects were not as clear-cut. While thyroid cancer rates were higher in girls than in boys exposed to the same dose of radiation in the Chernobyl studies [ 13 ], the sex difference appeared to be smaller than those reported from unexposed populations elsewhere [ 67 ]. This uncertainty echoes the CERRIE report [ 11 ] but may also be more specifically related to the specific incident.…”
Section: Effects Of Accidental Exposure To Internal Radiationmentioning
confidence: 99%
“…In addition to young age, female sex was also mentioned as an important risk factor, but while the studies on cancer incidence following Chernobyl agree that there is a significant negative correlation between age of exposure and elevated radiation-attributable thyroid cancer incidence [ 12 , 13 , 14 , 15 ], sex differences and hormonal effects were not as clear-cut. While thyroid cancer rates were higher in girls than in boys exposed to the same dose of radiation in the Chernobyl studies [ 13 ], the sex difference appeared to be smaller than those reported from unexposed populations elsewhere [ 67 ]. This uncertainty echoes the CERRIE report [ 11 ] but may also be more specifically related to the specific incident.…”
Section: Effects Of Accidental Exposure To Internal Radiationmentioning
confidence: 99%
“…We also extracted data on other high-radiation procedures using claims for cardiac catheterizations and common nuclear medicine procedures. 42 , 43 …”
Section: Methodsmentioning
confidence: 99%
“…We conducted sensitivity analyses using lag periods of 1–4 years and including the total number of other high-radiation procedures as a covariable in the model. 42 , 43 …”
Section: Methodsmentioning
confidence: 99%